1994
DOI: 10.3382/ps.0730224
|View full text |Cite
|
Sign up to set email alerts
|

Dietary and Environmental Factors Affecting Skin Strength in Broiler Chickens

Abstract: Two experiments were conducted to evaluate dietary and environmental factors involved in skin tensile strength of commercial broilers. In Experiment 1 the effect of added dietary fat (4 or 7%), environmental temperature (25 or 20.5 C after 21 d), and anticoccidial drug (halofuginone or salinomycin fed continuously) were examined factorially using male and female chicks. Skin tensile strength was measured at 21, 35, and 40 d of age. Thickness of the dermal layers was measured from skin taken at Day 35. In Exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
15
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 15 publications
4
15
0
Order By: Relevance
“…Meyer et al (2003a) also reported that the average fat-free skin weight of male ostriches was heavier than that of female ostriches. It was found that male broiler chickens had slightly thinner skins, but that the thickness of the dermal layer was higher in males than in females (Christensen et al, 1994). Males also had stronger skins than females.…”
Section: Discussionmentioning
confidence: 93%
“…Meyer et al (2003a) also reported that the average fat-free skin weight of male ostriches was heavier than that of female ostriches. It was found that male broiler chickens had slightly thinner skins, but that the thickness of the dermal layer was higher in males than in females (Christensen et al, 1994). Males also had stronger skins than females.…”
Section: Discussionmentioning
confidence: 93%
“…Male broiler chickens are more likely to develop breast blisters (Proudfoot et al, 1979) even when males and females of the same body weight are compared (Gyles et al, 1957;Stephenson et al, 1960). Differences between sexes in the propensity to develop breast blisters as well as scabby hip may be due to differences in onset of feathering (Siegel et al, 1957) or in the quality of the skin; however, males have been found to have stronger skin than female birds (Christensen et al, 1994). Scabby hip is not related to wet litter, unlike contact dermatitis, and is more readily visible than cellulitis (Norton, 1997).…”
Section: Breast Blisters In Broilersmentioning
confidence: 94%
“…Thickness and area of dermis were greater under normal TEM and G; although it is not known why reduced G and elevated TEM induced similar dermis development, it was also observed that dermis development of ducks coming from eggs incubated with normal TEM was negatively affected by hypoxia conditions (reduced G). The dermal layer is especially important since this is where skin collagen is located and is, therefore, directly related to skin resistance to breakage [32,33]. On overall papillae structure (Table 5), only height was affected (P<0.001) by a treatment interaction.…”
Section: Hatchability Bw Residual Yolk and Footpad Skin Developmenmentioning
confidence: 98%